Preparation method of germanium triphosphide nanosheet and application of germanium triphosphide film

Through high-temperature and high-pressure technology and electrochemical dissociation technology, high-purity, large-size single crystals of germanium triphosphide and two-dimensional germanium triphosphide nanosheets were prepared, solving the purity and size of germanium triphosphide materials in the existing technology, and significantly improving its energy storage performance and fast charging and discharging capabilities in supercapacitors.

CN119551636AActive Publication Date: 2025-03-04SHANDONG SUPER CRYSTAL NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411717978.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The prior art is difficult to prepare high-purity and large-size single crystals of germanium triphosphide, which makes it difficult to obtain two-dimensional germanium triphosphide materials, limiting its application in energy storage and other fields.

Method used

The high-temperature and high-pressure technology combined with electrochemical dissociation technology is used to prepare centimeter-level germanium triphosphide single crystals through high-temperature and high-pressure sintering, and micron-scale two-dimensional germanium triphosphide nanosheets are obtained through electrochemical dissociation technology.

Benefits of technology

The preparation of high-purity and large-size germanium triphosphine single crystals has been achieved, providing high-quality original materials for subsequent two-dimensional materials research, and through the two-dimensional germanium triphosphine nanosheet electrode material, the energy storage performance and fast charging and discharge capacity of the supercapacitor are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551636A_ABST
    Figure CN119551636A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a germanium triphosphide nanosheet, and belongs to the technical field of electrode material preparation. The preparation method comprises the following steps: step 1), pre-pressing mixed powder formed by red phosphorus powder and germanium powder to obtain a pre-pressed body; (2) carrying out high-temperature and high-pressure sintering on the pre-pressed body prepared in the step (1) to obtain bulk-phase germanium triphosphide; (3) taking the bulk-phase germanium triphosphide prepared in the step (2) as an electrode, and putting the bulk-phase germanium triphosphide into an electrolytic tank; 4) applying voltage or current to the electrode in the step 3) to perform intercalation dissociation on the germanium triphosphide; and (5) centrifuging the electrolyte subjected to electrochemical dissociation in the step (4), and collecting supernate to obtain the germanium triphosphide nanosheet. A large number of high-purity micron-sized germanium triphosphide nanosheets are prepared by combining a high-temperature and high-pressure technology with an electrochemical dissociation technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode material preparation, and in particular to a method for preparing germanium phosphide nanosheets and application of germanium phosphide thin films prepared from germanium phosphide nanosheets prepared by the preparation method in electrodes of supercapacitor energy storage devices. Background Art

[0002] In recent years, two-dimensional GeP3 crystals have attracted widespread attention in the field of materials science. Related research has progressed rapidly and has shown attractive prospects in the fields of energy storage, gas sensing and catalysis. GeP3 crystals have an arsenic honeycomb structure, and the atomic layers are stacked in an ABC manner by van der Waals forces. Its structure is similar to that of orthorhombic black phosphorus under high pressure. Each Ge atom in the GeP3 crystal layer forms a bond with three P atoms. The introduction of excess valence electrons of Ge atoms greatly improves the conductivity of the system. At a temperature of 25K, the conductivity of GeP3 is 1×10 6 Sm -1 , which is nearly a million times higher than black phosphorus. According to bond energy calculations, the P-Ge bond (bond energy: ~-5.3540eV) is weaker than the PP bond (bond energy: ~-7.0235eV), indicating that GeP3 crystals have a lower bulk modulus than black phosphorus and GeP5, and can more effectively alleviate the structural deformation caused by the charge and discharge process, thereby enhancing the cycle stability of the electrode material. In addition, weak interlayer interactions help two-dimensional materials to be obtained by mechanical or liquid phase peeling of the corresponding layered bulk materials.

[0003] In the field of electrochemical energy storage, GeP3 crystals, as electrode materials for lithium / sodium ion batteries, exhibit excellent energy storage performance due to their metal conductivity and dual-active energy storage components. Theoretical calculations show that the maximum theoretical capacity of a single-layer GeP3 is 648 mAhg -1 When combined with C material, it has an ultra-high reversible capacity of 1109 mAhg -1 , and exhibits excellent cycle characteristics and high rate capability.

[0004] At present, the main methods for synthesizing GeP3 compounds are high temperature and high pressure technology and high energy ball milling. Although high temperature and high pressure technology can be used to prepare high crystal quality, millimeter-scale germanium phosphorus series compounds, there is a problem of multiphase coexistence. In recent years, many research groups at home and abroad have successfully prepared GeP3 nanopowders with uniform physical phases by solid-phase reaction during high energy ball milling. However, during high energy ball milling, repeated collisions will cause the sample lattice to relax, easily destroy the crystal structure, and it is impossible to obtain high-quality, large-scale GeP3 single crystals. Since most of the existing two-dimensional materials are separated from bulk layered materials, the single crystal quality and scale of bulk layered materials are important guarantees for the preparation of two-dimensional materials. At present, due to the lack of high-quality, large-scale GeP3 bulk materials, two-dimensional GeP3 materials are difficult to obtain by mechanical or liquid phase exfoliation methods, which greatly hinders the research progress on the application of two-dimensional GeP3 crystals. Summary of the invention

[0005] In view of this, in order to solve the technical problems of low purity and small grain size of bulk germanium phosphide materials prepared by the prior art, on the one hand, the present invention provides a method for preparing germanium phosphide nanosheets, which utilizes high temperature and high pressure technology combined with electrochemical dissociation technology to prepare a large number of high-purity germanium phosphide nanosheets with centimeter-level single crystal phase.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing germanium triphosphide nanosheets comprises the following steps:

[0008] Step 1), pre-pressing a mixed powder formed by red phosphorus powder and germanium powder to obtain a pre-pressed body;

[0009] Step 2), subjecting the pre-pressed body prepared in step 1) to high temperature and high pressure sintering to obtain bulk germanium triphosphide;

[0010] Step 3), using the bulk germanium triphosphide prepared in step 2) as an electrode and placing it in an electrolytic cell;

[0011] Step 4), applying voltage or current to the electrode in step 3) to perform intercalation dissociation of germanium triphosphide;

[0012] Step 5), centrifuging the electrolyte after electrochemical dissociation in step 4), collecting the supernatant to obtain germanium triphosphide nanosheets.

[0013] Preferably, in step 2), the high temperature and high pressure sintering conditions are: the high pressure is 2 GPa, and the sintering temperature is 600-1000°C.

[0014] Preferably, in step 4), the applied voltage is 3-10 V or the applied current is 0.1-3 mA, and the treatment time is 0.2-1 h.

[0015] Preferably, in step 1), the molar ratio of germanium powder to red phosphorus powder is 1:3 to 3.2.

[0016] Preferably, in step 3), bulk germanium triphosphide is used as an electrode, a platinum sheet is used as a counter electrode, and an alkaline solution is used as an electrolyte to form an electrolytic cell.

[0017] Preferably, the concentration of the electrolyte is 0.3-1M.

[0018] Preferably, after step 4) and before step 5), the method further comprises:

[0019] Step 41), dispersing the electrolyte after electrochemical dissociation in step 4) into an organic solvent.

[0020] Preferably, the organic solvent is one or two of dimethyl sulfoxide, N-methylpyrrolidone, N-dimethylformamide, and dimethylacetamide.

[0021] Preferably, in step 1), the red phosphorus powder and the germanium powder are both ground powders.

[0022] On the other hand, the present invention also provides the use of a germanium phosphide thin film prepared from germanium phosphide nanosheets obtained by the method for preparing germanium phosphide nanosheets in electrodes of supercapacitor energy storage devices.

[0023] The method for preparing germanium phosphide nanosheets provided by the present invention utilizes high temperature and high pressure technology combined with electrochemical dissociation technology to prepare a large number of high-purity and micron-sized germanium phosphide nanosheets. Compared with the prior art, it has the following beneficial effects:

[0024] (1) The present invention uses a high temperature and high pressure sintering method to prepare centimeter-level germanium phosphide single crystals, and obtains two-dimensional germanium phosphide nanosheets with an average thickness of 4.5 nanometers through subsequent electrochemical dissociation technology, and the maximum radial dimension can reach 0.8 micrometers. High temperature and high pressure technology combined with electrochemical dissociation technology can obtain large-size, high-quality two-dimensional germanium phosphide nanosheets.

[0025] (2) The present invention overcomes the technical defect that it is difficult to prepare high-purity, large-size germanium phosphide single crystals, and realizes the preparation of high-purity germanium phosphide single crystals with a crystal size of up to 0.4 cm, providing raw materials for subsequent research on the physical properties of germanium phosphide crystals.

[0026] (3) The present invention adopts high temperature and high pressure technology to realize the preparation of germanium phosphide single crystal. Compared with the traditional gas phase method and ball milling method, its production cycle is short, the crystal size is large, and the crystal purity is high.

[0027] (4) The present invention can prepare germanium phosphide crystals in large quantities. By expanding the high-temperature and high-pressure cavity, the preparation of gram-level germanium phosphide crystals can be achieved at one time, which is of great significance for the subsequent research on germanium phosphide crystals.

[0028] (5) The present invention uses high-quality, large-size germanium phosphide crystals prepared at high temperature and high pressure as a precursor for electrochemical dissociation, which can ensure the preparation of micron-level two-dimensional germanium phosphide nanosheets.

[0029] (6) The two-dimensional germanium phosphide nanosheet electrode material prepared based on the present invention has high conductivity and high ion mobility, and thus has excellent energy storage performance, and its volume capacitance can reach 46.67F cm -3 , which is higher than the volume capacitance of black phosphorus nanosheets (17.8 F cm -3 ), and the two-dimensional germanium phosphide nanosheet supercapacitor can withstand 1000V s -1 The voltage sweep rate is higher than that of black phosphorus supercapacitors (which can only withstand 10V s -1 ), showing excellent fast charge and discharge capabilities. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 XRD patterns of samples obtained when the sintering temperatures in Examples 1-3 are 600° C., 800° C. and 1000° C., respectively;

[0031] Figure 2 The optical photographs and scanning electron microscope images of the high-quality, large-sized germanium triphosphide crystal obtained in Example 1 are shown; wherein (a) is an optical photograph of the high-quality, large-sized germanium triphosphide crystal obtained; (b) is a scanning electron microscope image;

[0032] Figure 3 The atomic force microscope image (a) and the thickness (b) and radial scale statistics (c) of the germanium phosphide nanosheets dissociated by the electrochemical dissociation technique in Example 5;

[0033] Figure 4 Atomic force microscope images (a), (d), (g) and thickness (b), (e), (h) and radial scale statistics (c), (f), (i) of germanium phosphide nanosheets dissociated using N-methylpyrrolidone solvent acetone and ethanol solution in Example 7;

[0034] Figure 5 (a) transmission image, (b) high-resolution image and (c) diffraction spot image of the two-dimensional germanium triphosphide nanosheet in Example 5;

[0035] Figure 6 This is a graph showing the change in volume capacitance of the two-dimensional germanium triphosphide nanosheets in Example 5 as a function of scan rate. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing germanium triphosphide nanosheets, comprising the following steps:

[0037] Step 1), pre-press the mixed powder formed by red phosphorus powder and germanium powder to obtain a pre-pressed body. In this step, the red phosphorus powder and the germanium powder are both ground powders. Specifically, the red phosphorus powder and the germanium powder can be manually ground in a vacuum glove box. The grinding particle size is preferably in the micron level.

[0038] This step can be implemented by any method in the prior art, for example, the mixed powder of red phosphorus powder and germanium powder obtained by manual grinding is placed in a steel mold and pressed into a block by a tablet press. The pressure used in the pressing process of pressing into a block can be any pressure that can press the powder obtained by manual grinding into a dense block; considering factors such as cost, under normal circumstances, a pressure of 1-20MPa can be used. The pre-pressed body is preferably a cylinder with a diameter of 14mm.

[0039] In this step, the molar ratio of germanium powder to red phosphorus powder is preferably 1:3 to 3.2.

[0040] Step 2), fill the pre-pressed body prepared in step 1) into a high-temperature and high-pressure reaction chamber, perform high-temperature and high-pressure sintering, and obtain bulk germanium phosphide. In this step, the high-temperature and high-pressure sintering conditions are: the high pressure is 2Gpa, and the sintering temperature is 600-1000℃. The sintering temperature is a key factor affecting the purity and grain size of bulk germanium phosphide; under a sintering pressure of 2GPa, the optimal temperature for obtaining high-purity and large-size germanium phosphide is 600℃; and a slow cooling method is adopted. As the temperature increases, germanium phosphide decomposes into black phosphorus, GeP and GeP5, and when the temperature decreases, the germanium phosphide grains cannot grow. In this step, in order to increase the size of germanium phosphide single crystals, the cooling rate can be controlled to 1-50℃ / min.

[0041] Step 3), the bulk germanium phosphide prepared in step 2) is used as an electrode and placed in an electrolytic cell. In this step, preferably the bulk germanium phosphide is used as an electrode, the platinum sheet is used as a counter electrode, and the alkaline solution is used as an electrolyte to form an electrolytic cell. The concentration of the electrolyte is preferably 0.3-1M.

[0042] Step 4), applying voltage or current to the electrode of step 3) to intercalate and dissociate germanium phosphide. This step is the electrochemical dissociation step, in which the applied voltage is 3-10V or the current is 0.1-3mA, and the processing time is 0.2-1h. The choice of electrolyte mainly depends on whether the ions in the solution can be inserted into the interlayer of germanium phosphide and expand it to achieve dissociation. The choice of voltage is determined by the thickness and radial size of the final product, two-dimensional germanium phosphide nanosheets. When a voltage of 3V is used, the average thickness of the prepared two-dimensional germanium phosphide nanosheets is 4.5 nanometers, and the maximum radial dimension can reach 0.8 microns; when a voltage of 5V is used, the thickness of the prepared two-dimensional germanium phosphide nanosheets is mostly above 10 nanometers, and the radial size is in the range of hundreds of nanometers.

[0043] Step 5), the electrolyte after electrochemical dissociation in step 4) is subjected to high-speed centrifugation, and the supernatant is collected to screen out germanium phosphide nanosheets with uniform size, which are two-dimensional germanium phosphide nanosheets.

[0044] Step 6) Prepare germanium phosphide thin film by vacuum filtration technology, and apply it to two-dimensional germanium phosphide nanosheet electrode of supercapacitor energy storage device.

[0045] In the present invention, after step 4) and before step 5), the method further comprises:

[0046] Step 41), dispersing the electrolyte after electrochemical dissociation in step 4) into an organic solvent.

[0047] The organic solvent is preferably one or two of dimethyl sulfoxide, N-methylpyrrolidone, N-dimethylformamide, and dimethylacetamide.

[0048] In the present invention, after step 4) and before step 41), the method further includes filtering and washing the germanium triphosphide electrolyte after electrochemical dissociation in step 4).

[0049] On the other hand, the present invention also provides the use of a germanium phosphide thin film prepared from a germanium phosphide nanosheet prepared by the method for preparing the above-mentioned germanium phosphide nanosheet in an electrode of a supercapacitor energy storage device. That is, the present invention first uses the method for preparing the germanium phosphide nanosheet to prepare a two-dimensional germanium phosphide nanosheet, then prepares the two-dimensional germanium phosphide nanosheet into a germanium phosphide thin film by vacuum filtration technology, and applies the germanium phosphide thin film to an electrode of a supercapacitor energy storage device.

[0050] The technical solution of the present invention is described clearly and in detail below in conjunction with specific implementation methods.

[0051] Example 1

[0052] (1) Using germanium powder and red phosphorus powder as raw materials, grinding is performed in a glove box. Preferably, the molar ratio of germanium powder to red phosphorus powder is 1:3. Preferably, in order to fully grind and mix the germanium powder and red phosphorus powder evenly, the grinding time is 60 minutes.

[0053] (2) The mixed powder is placed in a steel mold and pressed into a block using a tablet press; the pressure used in the pressing process is 10 MPa.

[0054] (3) subjecting the pressed block to high temperature and high pressure sintering: the molar ratio of the sintered mixed powders of germanium powder and red phosphorus powder is 1:3, the medium sintering pressure is 2 GPa, the heating rate is controlled to be 10°C / min, and the heating is stopped when the sintering temperature reaches 600°C, and the sintering is maintained at 600°C for 30 minutes; thus, a dense block is obtained.

[0055] (4) Bulk germanium phosphide synthesized under high pressure is used as an electrode.

[0056] (5) Germanium phosphide was placed in 40 ml of electrolyte and electrolyzed for 1 hour with a voltage of 5 V, thereby obtaining germanium phosphide nanosheets.

[0057] (6) The stripped solution is subjected to high-speed centrifugation at a centrifugal rate of 5000 rpm for 30 minutes to screen out two-dimensional germanium triphosphide nanosheets.

[0058] (7) The supernatant after centrifugation is taken and vacuum filtered using an organic microporous micromembrane with a diameter of 0.2 μm. After washing with deionized water, a two-dimensional germanium triphosphide nanosheet film is obtained after vacuum drying.

[0059] Figure 2 (a) is an optical picture of a high-quality, large-size germanium triphosphide crystal obtained in Example 1. Figure 2 (b) SEM image shows a clear layered structure. The largest Germanium Phosphide flake is as high as 0.3 cm, which is much larger than the hundred-nanometer-level Germanium Phosphide particles prepared by ball milling.

[0060] Example 2

[0061] (1) Using germanium powder and red phosphorus powder as raw materials, grinding is performed in a glove box. Preferably, the molar ratio of germanium powder to red phosphorus powder is 1:3. Preferably, in order to fully grind and mix the germanium powder and red phosphorus powder evenly, the grinding time is 60 minutes.

[0062] (2) The mixed powder is placed in a steel mold and pressed into a block using a tablet press; the pressure used in the pressing process is 10 MPa.

[0063] (3) The pressed block is subjected to high temperature and high pressure sintering: the molar ratio of the sintered mixed powders of germanium powder and red phosphorus powder is 1:3, the medium sintering pressure is 2 GPa, the heating rate is controlled to be 10°C / min, and the heating is stopped when the sintering temperature reaches 800°C, and the sintering is maintained at 800°C for 30 minutes; a dense block is obtained.

[0064] (4) Bulk germanium phosphide synthesized under high pressure is used as an electrode.

[0065] (5) Germanium phosphide was placed in 40 ml of electrolyte and electrolyzed for 1 hour with a voltage of 5 V, thereby obtaining germanium phosphide nanosheets.

[0066] (6) The stripped solution is subjected to high-speed centrifugation at a centrifugal rate of 5000 rpm for 30 minutes to screen out two-dimensional germanium triphosphide nanosheets.

[0067] (7) The supernatant after centrifugation was taken and vacuum filtered using an organic microporous micromembrane with a diameter of 0.2 μm. After washing with deionized water, a two-dimensional germanium triphosphide nanosheet film was obtained after vacuum drying.

[0068] Example 3

[0069] (1) Using germanium powder and red phosphorus powder as raw materials, grinding is performed in a glove box. Preferably, the molar ratio of germanium powder to red phosphorus powder is 1:3. Preferably, in order to fully grind and mix the germanium powder and red phosphorus powder evenly, the grinding time is 60 minutes.

[0070] (2) The mixed powder is placed in a steel mold and pressed into a block using a tablet press; the pressure used in the pressing process is 10 MPa.

[0071] (3) subjecting the pressed block to high temperature and high pressure sintering: the molar ratio of the sintered mixed powders of germanium powder and red phosphorus powder is 1:3, the medium sintering pressure is 2 GPa, the heating rate is controlled to be 10°C / min, and the heating is stopped when the sintering temperature reaches 1000°C, and the sintering is maintained at 1000°C for 30 minutes; thus, a dense block is obtained.

[0072] (4) Bulk germanium phosphide synthesized under high pressure is used as an electrode.

[0073] (5) Germanium phosphide was placed in 40 ml of electrolyte and electrolyzed for 1 hour with a voltage of 5 V, thereby obtaining germanium phosphide nanosheets.

[0074] (6) The stripped solution is subjected to high-speed centrifugation at a centrifugal rate of 5000 rpm for 30 minutes to screen out two-dimensional germanium triphosphide nanosheets.

[0075] (7) The supernatant after centrifugation was taken and vacuum filtered using an organic microporous micromembrane with a diameter of 0.2 μm. After washing with deionized water, a two-dimensional germanium triphosphide nanosheet film was obtained after vacuum drying.

[0076] The XRD patterns of the samples sintered at 600℃, 800℃ and 1000℃ are shown in Figure 2. Figure 1 When the sintering temperature is 600℃, the sample is pure germanium triphosphide. When the temperature rises to 800℃, a small amount of germanium phosphorus precipitates in the sample. When the temperature rises to 1000℃, a large amount of germanium phosphide (GeP) and black phosphorus (BP) appear in the sample. So we then choose the sample synthesized at 2GPa and 600℃ for electrolysis.

[0077] Example 4

[0078] (1) Using germanium powder and red phosphorus powder as raw materials, grinding was performed in a glove box. The molar ratio of germanium powder to red phosphorus powder was 1:3, and the grinding time was 60 min.

[0079] (2) The mixed powder was placed in a steel mold and pressed into a 14 mm cylinder using a tablet press; the pressure used in the pressing process was 10 MPa.

[0080] (3) The pressed cylinder is sintered at high temperature and high pressure: the molar ratio of the sintered mixed powders of germanium powder and red phosphorus powder is 1:3, the sintering pressure is 2 GPa, the sintering temperature is 600°C, the heating rate is controlled at 10°C / min, and the sintering time is 30 min.

[0081] (4) Bulk germanium phosphide synthesized under high pressure was used as an electrode, a platinum sheet was used as a counter electrode, and 0.6 M sodium hydroxide was used as an electrolyte.

[0082] (5) Germanium phosphide was placed in 40 ml of electrolyte and electrolyzed for 1 hour with a voltage of 3 V. Thus, germanium phosphide nanosheets were obtained.

[0083] (6) The stripped solution is subjected to high-speed centrifugation at a centrifugal rate of 5000 rpm for 30 minutes to screen out two-dimensional germanium triphosphide nanosheets of uniform size.

[0084] (7) The supernatant after centrifugation was taken and vacuum filtered using an organic microporous filter membrane with a diameter of 0.2 μm. After washing with deionized water, a two-dimensional germanium triphosphide nanosheet film was obtained after vacuum drying.

[0085] Example 5

[0086] (1) Using germanium powder and red phosphorus powder as raw materials, grinding is performed in a glove box. Preferably, the molar ratio of germanium powder to red phosphorus powder is 1:3. Preferably, in order to fully grind and mix the germanium powder and red phosphorus powder evenly, the grinding time is 30 minutes.

[0087] (2) The mixed powder is placed in a steel mold and pressed into a block using a tablet press; the pressure used in the pressing process is 10 MPa.

[0088] (3) subjecting the pressed block to high temperature and high pressure sintering: the molar ratio of the sintered mixed powders of germanium powder and red phosphorus powder is 1:3, the medium sintering pressure is 2 GPa, the heating rate is controlled to be 10°C / min, and the heating is stopped when the sintering temperature reaches 600°C, and the sintering is maintained at 600°C for 30 minutes; thus, a dense block is obtained.

[0089] (4) Bulk germanium phosphide synthesized under high pressure is used as an electrode.

[0090] (5) Germanium phosphide was placed in 40 ml of electrolyte and electrolyzed for 1 hour with a voltage of 5 V, thereby obtaining germanium phosphide nanosheets.

[0091] (6) The stripped solution is subjected to high-speed centrifugation at a centrifugal rate of 5000 rpm for 30 minutes to screen out two-dimensional germanium triphosphide nanosheets.

[0092] (7) The supernatant after centrifugation was taken and vacuum filtered using an organic microporous micromembrane with a diameter of 0.2 μm. After washing with deionized water, a two-dimensional germanium triphosphide nanosheet film was obtained after vacuum drying.

[0093] Figure 6 The two-dimensional germanium phosphide nanosheet prepared under the synthesis conditions of Example 5 is a graph showing the volume capacitance of the two-dimensional germanium phosphide nanosheet as a function of the scan rate. -1 At the scan rate, the volume capacitance of germanium phosphide nanosheets is as high as 46.67 F cm -3 , which is much higher than the volume capacitance of black phosphorus nanosheets and graphene (black phosphorus: 17.8Fcm -3 , graphene: 1F cm -3 ). Supercapacitors based on germanium phosphide nanosheets have excellent energy storage performance and fast charging and discharging capabilities, showing excellent commercial value.

[0094] The atomic force microscope image of the germanium phosphide nanosheets electrochemically dissociated under the conditions of Example 5 is as follows Figure 3 In (a), the thicknesses of the two nanosheets are 4.4 nm and 3.9 nm respectively. The thickness and radial dimensions of 100 nanosheets are shown in Figure 2. Figure 4 In (b) and (c), the average thickness of the nanosheets is 4.5 nm and the average radial size is 0.8 μm, indicating that two-dimensional germanium phosphide nanosheets can be effectively obtained by electrochemical dissociation technology.

[0095] Transmission image of two-dimensional germanium triphosphide nanosheets dissociated using electrochemical dissociation technology, such as Figure 5 In the figure (a), the nanosheets can be clearly seen. The corresponding high-resolution image (b) and diffraction spot image (c) Figure 5 Clear interference fringes can be seen in (b), and the lattice spacing from (c) corresponds to the (110), (210), and (120) planes respectively.

[0096] Example 6

[0097] (1) Using germanium powder and red phosphorus powder as raw materials, grinding is performed in a glove box. Preferably, the molar ratio of germanium powder to red phosphorus powder is 1:3. Preferably, in order to fully grind and mix the germanium powder and red phosphorus powder evenly, the grinding time is 60 minutes.

[0098] (2) The mixed powder is placed in a steel mold and pressed into a block using a tablet press; the pressure used in the pressing process is 10 MPa.

[0099] (3) subjecting the pressed block to high temperature and high pressure sintering: the molar ratio of the sintered mixed powders of germanium powder and red phosphorus powder is 1:3, the medium sintering pressure is 2 GPa, the heating rate is controlled to be 10°C / min, and the heating is stopped when the sintering temperature reaches 600°C, and the sintering is maintained at 600°C for 30 minutes; thus, a dense block is obtained.

[0100] (4) Bulk germanium phosphide synthesized under high pressure is used as an electrode.

[0101] (5) Germanium phosphide was placed in 40 ml of electrolyte and electrolyzed for 1 hour with a voltage of 10 V. Thus, germanium phosphide nanosheets were obtained.

[0102] (6) The stripped solution is subjected to high-speed centrifugation at a centrifugal rate of 5000 rpm for 30 minutes to screen out two-dimensional germanium triphosphide nanosheets.

[0103] (7) The supernatant after centrifugation was taken and vacuum filtered using an organic microporous micromembrane with a diameter of 0.2 μm. After washing with deionized water, a two-dimensional germanium triphosphide nanosheet film was obtained after vacuum drying.

[0104] Example 7

[0105] (1) Using germanium powder and red phosphorus powder as raw materials, grinding is performed in a glove box. Preferably, the molar ratio of germanium powder to red phosphorus powder is 1:3. Preferably, in order to fully grind and mix the germanium powder and red phosphorus powder evenly, the grinding time is 60 minutes.

[0106] (2) The mixed powder is placed in a steel mold and pressed into a block using a tablet press; the pressure used in the pressing process is 10 MPa.

[0107] (3) subjecting the pressed block to high temperature and high pressure sintering: the molar ratio of the sintered mixed powders of germanium powder and red phosphorus powder is 1:3, the medium sintering pressure is 2 GPa, the heating rate is controlled to be 10°C / min, and the heating is stopped when the sintering temperature reaches 600°C, and the sintering is maintained at 600°C for 30 minutes; thus, a dense block is obtained.

[0108] (4) Grind the bulk tin phosphide synthesized under high pressure into powder in a glove box.

[0109] (5) Tin phosphide is placed in 20 ml of N-methylpyrrolidone, ethanol or acetone organic solvent and subjected to ultrasonic liquid phase dissociation for 5 hours, thereby obtaining tin phosphide nanosheets.

[0110] (6) The stripped solution is subjected to high-speed centrifugation at a centrifugal rate of 5000 rpm for 30 minutes to screen out two-dimensional tin triphosphide nanosheets.

[0111] (7) The uniformly mixed suspension was taken and vacuum filtered using an organic microporous micromembrane with a diameter of 0.2 μm. After washing with deionized water, a two-dimensional tin triphosphide nanosheet film was obtained after vacuum drying.

[0112] Atomic force microscopy images of germanium phosphide nanosheets dissociated using liquid phase dissociation and N-methylpyrrolidone solvent, acetone and ethanol solution, respectively. Figure 4 In the figure, (a), (b) and (c) are atomic force microscopy images and thickness and radial scale statistics in N-methylpyrrolidone solvent solution; (d), (e) and (f) are atomic force microscopy images and thickness and radial scale statistics in acetone solvent solution; (g), (h) and (i) are atomic force microscopy images and thickness and radial scale statistics in ethanol solution; the thickness of the nanosheets dissociated in the three solutions is all above 9nm, and the radial size is relatively small.

Claims

1. A method for preparing germanium triphosphide nanosheets, characterized in that: The steps include: Step 1), pre-pressing a mixed powder formed by red phosphorus powder and germanium powder to obtain a pre-pressed body; Step 2), subjecting the pre-pressed body prepared in step 1) to high temperature and high pressure sintering to obtain bulk germanium triphosphide; Step 3), using the bulk germanium triphosphide prepared in step 2) as an electrode and placing it in an electrolytic cell; Step 4), applying voltage or current to the electrode in step 3) to perform intercalation dissociation of germanium triphosphide; Step 5), centrifuging the electrolyte after electrochemical dissociation in step 4), collecting the supernatant to obtain germanium triphosphide nanosheets.

2. The method for preparing germanium triphosphide nanosheets according to claim 1, characterized in that: In step 2), the high temperature and high pressure sintering conditions are: the high pressure is 2 GPa, and the sintering temperature is 600-1000°C.

3. The method for preparing germanium triphosphide nanosheets according to claim 1, characterized in that: In step 4), the applied voltage is 3-10 V or the current is 0.1-3 mA, and the treatment time is 0.2-1 h.

4. The method for preparing germanium triphosphide nanosheets according to claim 1, characterized in that: In step 1), the molar ratio of germanium powder to red phosphorus powder is 1:3-3.

2.

5. The method for preparing germanium triphosphide nanosheets according to claim 1, characterized in that: In step 3), bulk germanium triphosphide is used as an electrode, a platinum sheet is used as a counter electrode, and an alkaline solution is used as an electrolyte to form an electrolytic cell.

6. The method for preparing germanium triphosphide nanosheets according to claim 5, characterized in that: The concentration of the electrolyte is 0.3-1M.

7. The method for preparing germanium triphosphide nanosheets according to claim 1, characterized in that: After step 4) and before step 5), the method further includes: Step 41), dispersing the electrolyte after electrochemical dissociation in step 4) into an organic solvent.

8. The method for preparing germanium triphosphide nanosheets according to claim 7, characterized in that: The organic solvent is one or two of dimethyl sulfoxide, N-methylpyrrolidone, N-dimethylformamide and dimethylacetamide.

9. A method for preparing germanium triphosphide nanosheets according to any one of claims 1 to 8, characterized in that: In step 1), the red phosphorus powder and the germanium powder are both ground powders, and the particle size is approximately in the micron level.

10. Use of a germanium phosphide thin film prepared from germanium phosphide nanosheets prepared by the method for preparing germanium phosphide nanosheets according to any one of claims 1 to 9 in electrodes of supercapacitor energy storage devices.

Citation Information

Patent Citations

  • Two-dimensional layered GeP material as well as preparation method and application thereof

    CN111320153A

  • GeP nanosheet negative electrode for lithium ion battery and ultrasonic-assisted rapid stripping preparation method thereof

    CN113753870A

  • Saturable absorber based on two-dimensional germanium phosphide, preparation method of saturable absorber and optical fiber laser

    CN114725764A

  • Two-dimensional tin triphosphide nanosheet as well as preparation method and application thereof

    CN117486177A

  • Means for Augmenting the Performance of a Tire of a Ground or Flight Vehicle against Hazardous Tire-Disrupting Factors with the Means Disposed on the Outward Surface of the Wheel with the Tire Protected thereby mounted thereon and Concentrically or Eccentrically Revolvable with Respect to the Rotational Axis of the Wheel

    KR1020230070608A